Flow characteristic of an elliptically shaped piezoactuated micropump - Muhammad Zaim, Hassan (2010)
This project is an outcome of the work carried out in doing and completing final year project, design and analysis flow characteristic of an elliptically shaped piezoactuated micropump. This project is about the investigation of micropump system due to the flowrate of elliptical piezoactuated micro pump. It was started with an introduction in micropump design and structure. This method considers problem regarding valve and valveless types of micropump. After gathering all the relevant information, the project undergoes design process. The design was developed using SOLIDWORK 2010TM software based on the collected data. Several sketches have been made and only one was selected based on the suitability of the micropump and dimension of the nozzle and diffuser and the geometry of the elliptical micropump. The selected sketch was drawn in CAD software and simulates using CFD software. The result from simulation shows the design of micropump is fulfilled. After simulation, the micropump is fabricated. The fabrication is fully follows the specification of the elliptical micropump according to the design of micropump. The purpose of this fabrication is to develop an actual experiment to get the value of volume flowrate of an elliptically shaped of piezoactuated micropump. The result from the experiment shows with the increase of frequency, the volume flowrate also increase. Later on, flow characteristic of an elliptically shaped piezoactuated micropump can be determined. The design of micropump is successful as the investigation of the flow characteristic of an elliptically shaped piezoactuated micropump provides 0.5169μL/s for actuation frequency 25kHz, 0.4898μL/s for actuation frequency 15kHz and 0.4489μL/s for 5kHz actuation frequency. Throughout the investigation, the elliptical micropump is compared to another shape which are circular and square, the velocity through the gap for fluid to flow between membrane of piezoelectric and the body of micropump are be at variance. The micropump considered serves it purpose as it is successfully designed and fabricate.